Preference of Bangladesh university students for searching the library catalogue: OPAC or discovery tool?. Issue 4 (1st August 2016) - Yesmin, Shamima; Ahmed, S.M. Zabed
Abstract : Purpose: The aim of this paper was to compare university students' preferences for searching the library catalogue via the library's Koha online public access catalogue (OPAC) or its discovery tool VuFind. Design/methodology/approach: A total of 175 students responded to a questionnaire-based survey through which their demographic data, duration (years) of computer use and their self-reported levels of computer skills were obtained. Students were asked what interfaces they use for catalogue searching and to rate their opinion on the relevant interfaces on a seven-point Likert scale. Mann–Whitney and Kruskal–Wallis tests were conducted to statistically compare the differences between students' demographic/individual characteristics and their ratings on the respective interfaces. For those students who used both systems, differences between their Likert ratings were assessed using a one-tailed Wilcoxon signed rank test. Findings: The results showed that there were no significant differences among students in terms of their ratings on either the OPAC or VuFind interfaces. Wilcoxon signed ranks test indicated that significantly more students thought that VuFind was more usable than the Koha OPAC. Originality/value: This is a pioneering study of the current use of the OPAC and discovery tools by university students and their preferences for searching catalogue information through these systems. It is hoped that the findings of this study will encourage researchers to conduct task-based usability studies with various cataloguing tools and this could yield new and improved interaction designs for library catalogue searching.